Using zero tillage to ameliorate yield losses from weather shocks: Evidence from panel data in Haryana, India - Khan, Md. Tajuddin; Kishore, Avinash; Pandey, Divya; Joshi, Pramod Kumar (International Food Policy Research Institute, 2016)
Zero tillage (ZT) for wheat is one of the most widely adopted resource-conserving technologies in the rice-wheat systems in northern India. In areas of Haryana with rice-wheat systems, 36.5 percent of all farmers practice ZT on 35 percent of their wheat area. Yet the literature measuring the impact of ZT on farmers’ fields is scarce. This study fills this gap by using the data collected from a random sample of 717 farmers from 50 villages in 10 districts of Haryana. It applies the difference-in-differences method to five-year recall data on wheat yields in ZT and conventionally tilled plots of land to quantify the crop loss due to unseasonal rains right before wheat harvests in March 2015. The results reveal significantly lower wheat yield losses in the ZT plots than in the conventionally tilled plots. On average, farmers suffered yield losses ranging between 3.73 and 4.53 quintals per hectare in 2015 due to unseasonal rains. The loss was lower by 1.05–1.10 quintals per hectare in ZT plots. The analysis clearly shows that adoption of ZT helped in reducing crop loss in wheat by 24–28 percent, valued at 1,523–1,595 Indian rupees (Rs.) per hectare (approximately US$22.50 per hectare). The loss avoided due to ZT is nearly equal to the prevailing rental rate of the ZT machine (Rs. 1,500 per hectare) in Haryana. Climate models suggest that the incidence of short-duration acute hydro meteorological events is likely to increase in years to come. Such events are hard to predict and prepare for, and dealing with them hinges mainly on disaster relief. However, our results show that adoption of ZT is one possible way to reduce potential loss from some of these weather events and that ZT is therefore well characterized as a climate-smart technology.